Perceptions of athletes about gender inequality in futsal (Research, Society and Development, 2023)
Objective: to analyze the perception of athletes about gender inequality in the sport of futsal, in the countryside of Ceará. Method: qualitative approach, of the exploratory and descriptive type, carried out in 2022, with fifteen athletes futsal players, practicing the modality in public schools and futsal teams in Campos Sales, Ceará, Brazil. The collection of information occurred through individaul interview, with thematic analysis for the organization of information, a paritr of a table with the narratives of the participants, focusing on the themes: motivation, initiation, space of the woman in futsal and values framework. Results: The futsal athletes suffer prejudice, discrimination and gender inequality. However, it was verified that the persistence of the feminine practice in the sporting context is an act of resistance and, still, the feminine participation in futsal is shy in relation to the masculine and little relevant for the society. Conclusion: There are challenges that need to be overcome, such as the amplification of recognition, valorization and visibility of athletes, in addition to the need for sponsors to enable the professionalization of athletes and reduce gender inequality.